Innovation in Elementary School/Islamic Elementary School Curriculum Learning Models - Roso Murti; Moch. Farich Alfani (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
This research examines the need to improve the quality of education in elementary schools/Islamic elementary schools (SD/IS), which must be implemented through designing and creating creative and innovative learning models. The use of appropriate learning models can also create an effective learning environment. This is also a key point of change in a dynamic curriculum. In implementing the 2013 Curriculum in elementary schools/IS, several learning models can be applied, including the inquiry learning model, discovery learning model, project-based learning model, problem-based learning model, and cooperative learning model. Innovative elementary school/IS learning strategies in implementing the Merdeka Curriculum include: (1) the use of game-based learning (GBL); (2) multidimensional learning; (3) hybrid learning with parent involvement; (4) community-centered student learning; and (5) student-oriented learning. The implementation of the Independent Curriculum at the elementary and Islamic elementary school (SD/MI) level often utilizes project-based learning models. This is to support the achievement of the Pancasila-based student profile, which is a hallmark of the Independent Curriculum. In addition to the learning models from these two curricula, there are also learning models that teachers at the elementary and Islamic elementary school (SD/MI) can implement to prepare students for the Industrial Revolution 4.0 era, including mindful learning, experiential learning, transformational learning, immersive learning, the "High Tech, High Touch" approach, design thinking, storytelling, and STEAM-based learning (science, technology, engineering, art, and mathematics).